Magical Thinking, Fantastic Film, and the Illusions of Neoliberalism - Blouin, Michael J.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book analyzes how contemporary popular films with fantastic themes, including Candyman, Frozen, The Cabin in the Woods, and The Incredible Burt Wonderstone, cultivate neoliberal subjectivities. These films promise dramatic change, but they too often deliver more of the same. Although proponents maintain the illusion that the militant enforcement of free-market economics will resolve racism, climate change, and imperialism, their magical thinking actually fuels the crises. Magical Thinking, Fantastic Film, and the Illusions of Neoliberalism explores the ways in which the visual economies of Hollywood fantasy compliment this particular political economy.
1 Introduction: Neoliberal Fantasies -- 2 (Neo)liberalism and the Banal Apocalypse -- 3 Cinematic Enchantment and the Magic of the Market -- 4 Candyman and Neoliberal Racism -- 5 Climate Change and the "Greenwashing" of Hollywood Fantasies -- 6 American Horror, Global Commons, and The Cabin in the Woods -- 7 Biopolitics and Movies about Magic -- Coda: The Hunger Games, The Watchmen, and The Confused Critic. .
Keywords: Motion pictures-History.; Motion pictures-United States; Communication; Film genres; Arts; American Cinema and TV